Contos e brincadeiras : a integração de histórias infantis e jogos matemáticos na educação inclusiva - Vieira, Ise Helena Miguel de Oliveira (2025)
This research focused on the development of inclusive pedagogical materials, particularly thecreation of children's stories and educational games aimed at students with learning difficultiesand Autism Spectrum Disorder (ASD). The central question guiding the study is: Does thecombination of contextualized children's stories and playful activities promote the intellectualdevelopment of children with disabilities? The study is structured into three scientific articles,grounded in the theories of Lev Vygotsky and Mantoan, which provide a solid foundation forunderstanding child development within learning contexts. The first article, ActiveMethodologies in Early Childhood Education: A Case Study on the Inclusion of a Student withAutism, published in Revista Impacto, investigates the implementation of active methodologiesadapted to the educational needs of an autistic student, contributing to a broader understandingof diversity in inclusive education. The second article, Beyond the Label: Exploring theMultiple Dimensions of Autism, published in Revista Educação em Contexto, consists of ascientific literature review with an emphasis on aspects of Autism Spectrum Disorder (ASD)from 2009 to 2020. The third article (in press), titled Games and Children's Stories in InclusiveEducation: Strategies for Cognitive Development, presents the product of this research: twooriginal children's stories designed to foster the development of children with learningdifficulties and autism. The stories focus especially on skills related to addition, even and oddnumbers, as well as social, emotional, and cognitive aspects. Each story was developedalongside a corresponding game and accompanied by guides for teachers, parents, and specialeducation professionals, aiming to support inclusive pedagogical practices. The themes includemathematical content and prioritize sensory stimulation, alternative communication, and otherstrategies that respect each student's development and context. The educational product isintended to be shared with the school community, promoting the dissemination of inclusivepractices.